Tidal Modulation of the Gravitywave Momentum Flux in the Antarctic Mesosphere - Espy, P. J.; Jones, G. O.L.; Swenson, G. R.; Tang, J.; Taylor, Michael J. (Hosted by Utah State University Libraries, 2004)
Airglow imager and dynasonde/IDI radar wind measurements at Halley Station, Antarctica (76S, 27W) have been used to estimate the diurnal variation of the vertical fluxes of horizontal momentum carried by highfrequency atmospheric gravity waves. The cross-correlation coefficients between the vertical and horizontal wind perturbations were calculated from the sodium airglow imager data collected during four consecutive nights of near total darkness during July of 2000. These were combined with wind-velocity variances from coincident radar measurements to estimate the upper limit of the vertical flux of horizontal momentum during three-hour intervals throughout the period. The resulting momentum flux showed a marked semi-diurnal oscillation in the zonal and meridional components. Calculations of the momentum flux through the Na airglow show variations in period and phase consistent with the observations, implying that tidal propagation and modulated gravity-wave forcing may both affect observed wind variations. INDEX TERMS: 3332 Meteorology and Atmospheric Dynamics: Mesospheric dynamics; 3334 Meteorology and Atmospheric Dynamics: Middle atmosphere dynamics (0341, 0342); 3384 Meteorology and Atmospheric Dynamics: Waves and tides.